الطلبة الجامعيون الجزائريون وموقع الفيسبوك "دراسة في عادات وأنماط استخدام عينة من طلبة - عبادة, نور الهدى (Changement Social; No 05 (2018): revue change social, 2018)
نسعى من خلال هذا المقال إلى التعرف على أنماط استخدام عينة من طلبة جامعة الجزائر3 كلية علوم الإعلام والاتصال لموقع الفيسبوك، وذلك بعد التعرف أولا على خصائص عينة البحث من حيث:  الجنس والفئات العمرية والإقامة والحالة الاجتماعية، ثم أنماط الاستخدام من حيث، الأقدمية، مدة الاستخدام، عدد مرات تصفح الحساب الشخصي عبر موقع الفيسبوك،فترات استخدام الموقع، الوسيلة المفضلة لاستخدام الموقع، طبيعة أصدقاء المبحوثين عبر الموقع  معايير اختيار أفراد عينة البحث لأصدقائهم عبر الموقع، عدد الأصدقاء، طبيعة الاستخدام: بالمشاركة أو من دون مشاركة، الانخراط في مجموعات افتراضية واللغة المستخدمة. الكلمات المفتاحية: الطلبة الجامعيون، العادات، الأنماط، الاستخدام . We want from this article to identify the use patterns for a sample of the students from the University of Algiers3, Faculty of Information Sciences and communication to Facebook. This is after identifying the characteristics of the search sample: gender, age, residence and the social situation,Then, the use patterns of the seniority, duration of use, the number of times in browsing the personal account through Facebook, periods of using the site, the preferred means to use the site, the nature of the Friends for he respondents through the site, the criteria for selecting the members of the research sample for their friends through the site, the number of friends, the nature of Use: to participate or without participating, to engage in virtual groups and the used language. Keywords: University Students, habits, patterns, use.